The gender gap in the wage sensitivity of job transitions: A decomposition analysis - Céline Detilleux; Nick Deschacht (Journal for Labour Market Research, 2024)
Previous research shows that female workers are less sensitive to wages in their decision to switch jobs than male workers, and that this could explain a substantial part of the gender wage gap. This paper studies to what extent gender differences in preferences and personality traits explain the gender gap in the wage-elasticity of job-to-job transitions in the labor market. Using a novel decomposition approach in the context of mediated moderation and using German Socio-Economic Panel Survey (G-SOEP) data for the period 2005-2019, we find that gender differences in risk preferences, patience, trust, reciprocity, altruism, conscientiousness, ambition and self-esteem explain about 25% of the gender gap in wage-elasticities of job separations. A detailed decomposition suggests that risk preferences, trust and ambition contribute most to this gender gap in wage-elasticity.
Keywords: J16; J42; 330; Economic preferences; Gender; Mediation analysis; Monopsony power